2005
DOI: 10.1038/sj.emboj.7600916
|View full text |Cite
|
Sign up to set email alerts
|

CLIP-170 facilitates the formation of kinetochore–microtubule attachments

Abstract: CLIP-170 is a microtubule 'plus end tracking' protein involved in several microtubule-dependent processes in interphase. At the onset of mitosis, CLIP-170 localizes to kinetochores, but at metaphase, it is no longer detectable at kinetochores. Although RNA interference (RNAi) experiments have suggested an essential role for CLIP-170 during mitosis, the molecular function of CLIP-170 in mitosis has not yet been revealed. Here, we used a combination of high-resolution microscopy and RNAi-mediated depletion to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
89
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 35 publications
(68 reference statements)
15
89
0
Order By: Relevance
“…Although CLIP-170 depletion did not affect mitotic entry and exit, CLIP-170-depleted cells had significantly higher levels of phospho-H3-positive staining at 10, 12, and 14 h postrelease, indicating that CLIP-170 is involved in mitotic progression (data not shown). This is consistent with the published CLIP-170 loss-of-function phenotypic analysis (12). To assess the contribution of Cdc2 phosphorylation of CLIP-170 during mitosis, similar experiments were performed using U2OS cells stably expressing GFP-CLIP-170 (WT, T287A, or T287D) in the absence of endogenous CLIP-170 (Fig.…”
Section: Cdc2-mediated Phosphorylation Of Clip-170 Is Essential For Tsupporting
confidence: 71%
See 1 more Smart Citation
“…Although CLIP-170 depletion did not affect mitotic entry and exit, CLIP-170-depleted cells had significantly higher levels of phospho-H3-positive staining at 10, 12, and 14 h postrelease, indicating that CLIP-170 is involved in mitotic progression (data not shown). This is consistent with the published CLIP-170 loss-of-function phenotypic analysis (12). To assess the contribution of Cdc2 phosphorylation of CLIP-170 during mitosis, similar experiments were performed using U2OS cells stably expressing GFP-CLIP-170 (WT, T287A, or T287D) in the absence of endogenous CLIP-170 (Fig.…”
Section: Cdc2-mediated Phosphorylation Of Clip-170 Is Essential For Tsupporting
confidence: 71%
“…The role of CLIP-170 during mitosis was recently examined by loss-offunction approaches. It was shown that CLIP-170 localizes to unattached kinetochores in prometaphase and that such localization is essential for the formation of kinetochore-microtubule attachments (12,13).…”
mentioning
confidence: 99%
“…These results suggest that redundant pathways exist for spindle assembly and chromosome congression in mammalian cells. The prometaphase delay in myosin VI knockdown cells is very similar to the delay described recently for Clip 170 KD cells (Dujardin et al, 1998;Tanenbaum et al, 2006). Clip 170 was identified as a myosin VI binding partner in Drosophila (Lantz and Miller, 1998); however, in mammalian cells we have not been able to confirm by yeast two-hybrid or mammalian two-hybrid assays or by coimmunoprecipitation any interaction between myosin VI and Clip 170.…”
Section: Discussionmentioning
confidence: 53%
“…It has been described that overexpression of p50/dynamitin, a second dynactin subunit, eliminated NE invaginations of prophase cells (1). This result suggests that p150 Glued might be also involved in NEBD, as overexpression of p50/dynamitin is a standard approach to inhibit the function of p150 Glued in a dominant-negative fashion (11). Unfortunately, we could not directly analyze the effect of depletion of p150 Glued on NEBD, as p150 Glued -depleted cells failed to enter mitosis (Fig.…”
Section: Results P150mentioning
confidence: 65%